Tobacco use in Nigerian youth: A systematic review. - Bankole K Oyewole; Victor J Animasahun; Helena J Chapman (PLoS ONE)
Background Tobacco use is the most important preventable cause of premature death and major risk factor for non-communicable diseases. Due to strict tobacco legislation in the western hemisphere, many African nations like Nigeria have shifted from being a tobacco-producing nation to a tobacco-consuming one. The purpose of this study was to systematically review existing literature on tobacco use among Nigerian adolescents and young people and identify the prevalence, distribution and factors influencing of tobacco smoking. These data are necessary to formulate and adapt control measures aimed at tobacco cessation among young people, and preventing long-term smoking behaviors. Methods Three databases (African Journals Online, PsychInfo, PubMed) were searched for peer-reviewed publications, published between January 2000 and March 2017. Additional searches were completed on Google Scholar, and other documents and reports of the Nigerian government and the Global Youth Tobacco Survey were consulted. Using the PRISMA guidelines to evaluate studies, we included studies that reported prevalence of tobacco use in adolescents or youths, aged 10 to 24, and excluded evaluations of tobacco-related medical conditions. Results A total of 30 studies with a total population of 26,709 were reviewed. Prevalence rates of tobacco smoking ranged from 0.2% to 32.5%. Among the gender-specific studies, the prevalence of smoking among females ranged between 2.2% to 10% while that of males ranged from 1% to 32.5%. Gender distribution among these studies was mixed (80.0%), males only (13.3%) and females only (6.7%). Smoking prevalence was higher among males than females. The most common risk factors for tobacco use included peer influence, family conditions, psychosocial factors and male gender. Additional risk factors included concomitant substance abuse, media advertisements and increasing age. Conclusions Tobacco smoking poses a huge burden to Nigerian youths and various determinants were highlighted in this review. It is imperative that all stakeholders engage in concerted efforts to target both in-school and out-of-school youths in tobacco control strategies.